Preparation method for reducing oxidation burning loss of active elements in smelting process of Cu-Cr-Zr alloy

By using a combination of composite covering agent and a deoxidizing agent of Cu-Mg intermediate alloy, the problem of oxidation and burning of active elements during Cu-Cr-Zr alloy smelting is solved, and the preparation and production efficiency of high-quality alloys are improved.

CN119410938APending Publication Date: 2025-02-11KUNMING METALLURGY INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699860.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Cu-Cr-Zr alloys are prone to oxidation and burning of active elements during smelting, resulting in unstable material properties. Traditional vacuum smelting equipment is expensive, limiting the application of large-scale production.

Method used

Using a composite covering agent composed of charcoal, flake graphite and inorganic composite salt, combined with Cu-Mg intermediate alloy as a deoxidant, the melt is coated by forming a stable structure of multi-layer viscous substance to prevent oxidation and burning, and through deoxygenation reaction Reduce the oxygen content in the furnace.

Benefits of technology

It effectively reduces the oxidation and burning of active elements, improves the yield of Cr and Zr elements, ensures the uniform distribution and stable existence of alloy components, shortens the smelting time, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410938A_ABST
    Figure CN119410938A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for reducing oxidation burning loss of active elements in the smelting process of a Cu-Cr-Zr alloy, and belongs to the technical field of alloy smelting. The preparation method comprises the following steps: preparing materials according to a formula ratio, firstly adding Cu particles after baking, adding a covering agent when the Cu particles begin to melt, and regulating the temperature to 1150-1250 DEG C after all molten copper is melted down; a deoxidizing agent Cu-Mg intermediate alloy is added, and a covering agent is supplemented; and a Cu-Cr intermediate alloy is added, a covering agent is supplemented, heat preservation smelting is conducted for 20-30 min, and the temperature is adjusted to 1250-1350 DEG C. And adding the deoxidizing agent Cu-Mg intermediate alloy again, supplementing the covering agent, adding the Cu-Zr intermediate alloy, supplementing the covering agent, carrying out heat preservation smelting for 20-30 minutes, and regulating the temperature to 1150-1250 DEG C. And after slagging-off, pouring is conducted, and the Cu-Cr-Zr alloy is obtained. According to the method, the defects that alloy components are not uniform and unmelted metal particles are contained can be overcome, the quality and comprehensive performance of the alloy material are improved, the yield of Cr and Zr elements is greatly increased while the oxidation burning loss of active elements is reduced, the yield of the Cr element is larger than or equal to 84%, and the yield of the Zr element is larger than or equal to 50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy smelting, and in particular relates to a preparation method for reducing oxidation and burning loss of active elements in a Cu-Cr-Zr alloy smelting process. Background Art

[0002] Copper-chromium-zirconium (Cu-Cr-Zr) alloy is a kind of functional structural material with excellent physical and mechanical properties, known for its high strength, excellent electrical and thermal conductivity, and excellent corrosion resistance. These properties make it play a key role in the fields of nuclear power equipment manufacturing, large integrated circuit lead frames, high-speed railway contact network materials, resistance welding electrodes and continuous casting molds.

[0003] In the smelting process of copper and copper alloys, there are often common problems such as oxidation, gas absorption and impurity absorption, which seriously pollute the melt, weaken the comprehensive performance of the material and the quality of the final product. The traditional preparation of Cu-Cr-Zr alloy mainly adopts the vacuum melting method, which needs to be carried out at high temperature. By preventing oxidation and gas absorption, the purity of the alloy liquid composition is improved, and the influence of abnormal structure, inclusions and other defects on the electrical conductivity and thermal conductivity of the material is avoided, while ensuring the uniform distribution of each component in the alloy. However, due to the high melting point and easy oxidation characteristics of Cr and Zr, component burning and oxidation are prone to occur during vacuum melting. This not only increases the production cost, but also affects the performance stability of the alloy. In addition, the vacuum melting equipment is expensive, which seriously limits its application in large-scale production.

[0004] Domestic non-vacuum melting technology for Cu-Cr-Zr alloys is still in the research stage, with the following characteristics: First, charcoal is generally selected as a covering agent, which is sintered to reduce the amount of copper liquid absorbed. However, this covering agent is only suitable for small furnace smelting and short-term smelting. It is not suitable for large furnace smelting and mass production, which will lead to a large amount of alloy element burnout. Secondly, after slagging and furnace discharge, the Cu-Zr alloy is added by punching and melting in the ladle. The method of punching and melting in the ladle may result in uneven alloy composition and even contain unmelted metal. Therefore, it is necessary to develop a non-vacuum melting method for Cu-Cr-Zr alloys with simplified process flow and high production efficiency, reduce the oxidation and burning of active elements during the smelting process, and obtain high-quality copper alloy materials. Summary of the invention

[0005] The object of the present invention is to provide a preparation method for reducing oxidation and burning loss of active elements in the Cu-Cr-Zr alloy smelting process.

[0006] The object of the present invention is achieved in this way: the preparation method for reducing the oxidation and burning loss of active elements in the Cu-Cr-Zr alloy smelting process includes material preparation, refining and casting processes, specifically including: A. Material preparation: according to the composition design requirements, weigh Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy for use.

[0007] B. Refining: Bake the furnace, add Cu particles, and add the covering agent when it starts to melt. After all the copper liquid is melted, adjust the temperature to 1150~1250℃; Add deoxidizer Cu-Mg master alloy and fill in covering agent to cover the melt; Add Cu-Cr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1250-1350℃; Add deoxidizer Cu-Mg master alloy again, and add covering agent to cover the melt; Add Cu-Zr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1150-1250℃.

[0008] C. Casting: slag removal and casting to obtain Cu-Cr-Zr alloy.

[0009] Compared with the prior art, the technical solution of the present invention has the following outstanding substantial features and significant progress: The existing melting and casting technology uses charcoal as a covering agent, which is calcined to reduce the amount of gas absorbed by the copper liquid. This covering agent is only suitable for small furnace smelting and short-term smelting, and is not suitable for large furnace smelting and mass production. It may even cause problems such as large alloy element burnout.

[0010] The technical solution of the present invention uses a composite covering agent composed of charcoal, flake graphite and inorganic composite salt, with the inorganic composite salt as the bottom layer, and charcoal and flake graphite as the upper layer. A stable structure is formed through complex reactions at high temperature, and transformed into a multi-layer viscous substance, which can be well coated on the surface of the melt, so that the melt in the furnace forms a false vacuum state, which can well prevent atmospheric gases from diffusing to the surface of the melt through the covering layer or directly causing oxidation and burning of the melt. This multi-layer viscous substance also has the function of a thermal insulation layer, which reduces the unevenness of the temperature field in the furnace, can avoid overheating of the alloy liquid, reduce smelting losses, is conducive to the uniform distribution and stable existence of alloy elements, and shortens the smelting time.

[0011] The technical solution of the present invention uses a Cu-Mg intermediate alloy that is more easily oxidized than alloy elements as a deoxidizer to deoxidize the gas with certain oxidation loss and a large amount of copper oxide in the smelting furnace and the melt. Mg reacts easily with oxygen at high temperatures to generate stable magnesium oxide (MgO), thereby consuming the oxygen in the furnace. This deoxidation not only reduces the oxygen content in the furnace, but also forms a layer of magnesium oxide covering layer, further isolating the alloy from the air and preventing the oxidation and burning of Cr and Zr elements. In addition, the multi-layer covering agent effectively blocks the air from entering the melt, effectively maintaining the stability of the oxygen content in the melt, and the oxygen in the melt reacts with the deoxidizer alloy elements to reach equilibrium, thereby hindering the oxidation process and avoiding the oxidation and burning of Cr and Zr in the later stage of smelting.

[0012] The composite covering agent and deoxidizer are used at the same time, and Cu, Cu-Cr and Cu-Zr can be added to the melt in the order of smelting, avoiding the defects of uneven alloy composition and unmelted metal particles caused by the existing melting and casting technology method, and improving the quality and comprehensive performance of the alloy material. Under the dual effects of the covering agent and the deoxidizer, while reducing the oxidation and burning of active elements, the recovery rate of Cr and Zr elements is greatly improved, so that the recovery rate of Cr elements is ≥84%, even up to 90%, and the recovery rate of Zr elements is ≥50%, even up to 69%. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a surface scanning energy spectrum of the ingot in Example 1 in which the raw materials were not subjected to the oxidation layer removal treatment during smelting, and both the covering agent and the deoxidizing agent were used; Figure 2 This is a surface scanning energy spectrum of the ingot in Example 2 in which the raw materials have been treated to remove the oxide layer during smelting, and both the covering agent and the deoxidizer have been used. DETAILED DESCRIPTION

[0014] The present invention is further described below, but the present invention is not limited in any way. Any changes or substitutions made based on the teachings of the present invention belong to the protection scope of the present invention.

[0015] The preparation method for reducing oxidation and burning loss of active elements in the Cu-Cr-Zr alloy smelting process includes material preparation, refining and casting processes, specifically including: A. Material preparation: according to the composition design requirements, weigh Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy for use.

[0016] B. Refining: Bake the furnace, add Cu particles, and add the covering agent when it starts to melt. After all the copper liquid is melted, adjust the temperature to 1150~1250℃; Add deoxidizer Cu-Mg master alloy and fill in covering agent to cover the melt; Add Cu-Cr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1250-1350℃; Add deoxidizer Cu-Mg master alloy again, and add covering agent to cover the melt; Add Cu-Zr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1150-1250℃.

[0017] C. Casting: slag removal and casting to obtain Cu-Cr-Zr alloy.

[0018] The method may further include an oxide layer removal process, specifically: electrolytically polishing the Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy weighed according to the component design requirements, and then cleaning and drying them as smelting raw materials for standby use. Electrolytic polishing can remove the oxide layer and oil stains on the surface of the raw materials. Cleaning and drying can be done with anhydrous ethanol and vacuum drying. This process can further avoid the introduction of inclusions and oxidation burning caused by the oxide layer and oil stains of the raw materials during the smelting process.

[0019] The composition design requirement means that the composition content ratio of the Cu-Cr-Zr alloy is: the mass percentage of Cr is 1.0%, the mass percentage of Zr is 0.2%, and the balance is Cu.

[0020] The covering agent is composed of charcoal, flake graphite, and inorganic composite salt. Before adding, the covering agent is dehydrated and dried to make the moisture content less than 0.5%. Among the covering agent components, the mass ratio of charcoal, flake graphite, and inorganic composite salt is 1:1:3. The order of adding the components of the covering agent is: first add the inorganic composite salt as the bottom layer, then add charcoal and flake graphite as the upper layer, and the total thickness of the covering layer is 2-60 mm.

[0021] In the covering agent, the inorganic composite salt is any one of sodium fluoroaluminate, calcium chloride, sodium chloride or potassium chloride.

[0022] The first addition amount of the deoxidizer Cu-Mg master alloy is 0.5-1% of the mass of the melt; the second addition amount is 0.5-1% of the mass of the melt.

[0023] In the Cu-Cr-Zr alloy, the mass percentage of Cr is 1.0%, the mass percentage of Zr is 0.2%, and the balance is Cu. The yield of the Cr element is ≥84%, and the yield of the Zr element is ≥50%.

[0024] Example 1 Through composition design, the Cu-1Cr-0.2Zr alloy composition was designed, with the mass percentage of Cr being 1.0%, the mass percentage of Zr being 0.2%, and the balance being Cu.

[0025] A. Material preparation: Before smelting, weigh Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy according to the composition design requirements.

[0026] B. Refining: Add high-purity Cu particles to the furnace, and when they begin to melt, add fully dried covering agent with a moisture content of less than 0.5%. The mass ratio of charcoal, flake graphite, and inorganic composite salt in the covering agent is 1:1:3. When adding, first add the inorganic composite salt as the bottom layer, then add charcoal and flake graphite as the upper layer, and the total thickness of the covering layer is 2~60mm. After all the copper liquid is melted, adjust the temperature to 1150~1250℃; Add 1% of the melt mass of deoxidizer Cu-Mg master alloy for deoxidation and degassing, and add covering agent to cover the melt; Add Cu-Cr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1250-1350℃; 1% of the melt mass of deoxidizer Cu-Mg master alloy is added again for deoxidation and degassing treatment, and a covering agent is added to cover the melt; Add Cu-Zr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1150-1250℃.

[0027] C. Casting: slag removal and casting to obtain Cu-Cr-Zr alloy.

[0028] The obtained Cu-Cr-Zr alloy ingot was cut and sampled, and its cross section was subjected to surface scanning energy spectrum analysis, as shown in the attached Figure 1 As shown. When the raw material is not treated to remove the oxide layer, but the covering agent and deoxidizer are used, the covering agent can form a viscous substance, which can contact the surface of the melt well, form a good covering state, isolate the melt from the atmosphere to form a false vacuum state to block the entry of oxygen, and prevent the oxygen in the air from penetrating into the melt and reacting with the active elements Cr and Zr in the melt; the addition of Cu-Mg deoxidizer is mainly based on the fact that the oxidation activity of Cu-Mg master alloy is much higher than that of Cr and Zr, and Cu-Mg preferentially consumes the surface oxide layer of the raw material and oxygen in the melt by sacrificing Mg; under the joint action of the covering agent and the deoxidizer, the oxygen content in the melt can be stably maintained, and the reaction of oxygen in the melt with the alloy elements tends to a balanced state, thereby effectively hindering the oxidation process, reducing the oxidation and burning rate of Cr and Zr elements, and the recovery rate of Cr and Zr elements can be as high as 84% ​​and 50%.

[0029] The calculation method of the yield rate is: the percentage of the mass of Cr and Zr elements in the ingot after pouring and the mass of Cr and Zr elements added during the smelting process. The calculation formula is as follows: C=(M d ×d) / (M m ×b)×100% Where C is the alloy element yield, M d is the mass of the ingot after pouring, d is the mass percentage of the alloying element in the ingot, M m is the mass of the master alloy, and b is the mass percentage of the alloying elements in the master alloy.

[0030] In summary, compared with the traditional melting and casting technology, the recovery rates of Cr and Zr elements using the non-vacuum preparation technology of the present invention can be as high as 84% ​​and 50%.

[0031] The method may further include an oxide layer removal process, specifically: electrolytically polishing the Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy weighed according to the component design requirements, and then cleaning and drying them as smelting raw materials for standby use. Electrolytic polishing can remove the oxide layer and oil stains on the surface of the raw materials. Cleaning and drying can be done with anhydrous ethanol and vacuum drying. This process can further avoid the introduction of inclusions and oxidation burning caused by the oxide layer and oil stains of the raw materials during the smelting process.

[0032] Example 2 The composition design is the same as that in Example 1.

[0033] A. Material preparation: Before smelting, weigh Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy according to the composition design requirements. Electropolish the weighed Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy to remove the oxide layer and oil on the surface of the raw materials, clean them with anhydrous ethanol, and dry them in a vacuum environment at 200℃ before using them as smelting raw materials.

[0034] B. Refining: Add high-purity Cu particles to the furnace, and when they begin to melt, add fully dried covering agent with a moisture content of less than 0.5%. The mass ratio of charcoal, flake graphite, and inorganic composite salt in the covering agent is 1:1:3. When adding, first add the inorganic composite salt as the bottom layer, then add charcoal and flake graphite as the upper layer, and the total thickness of the covering layer is 2~60mm. After all the copper liquid is melted, adjust the temperature to 1150~1250℃; Add 1% of the melt mass of deoxidizer Cu-Mg master alloy for deoxidation and degassing, and add covering agent to cover the melt; Add Cu-Cr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1250-1350℃; 1% of the melt mass of deoxidizer Cu-Mg master alloy is added again for deoxidation and degassing treatment, and a covering agent is added to cover the melt; Add Cu-Zr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1150-1250℃.

[0035] C. Casting: slag removal and casting to obtain Cu-Cr-Zr alloy.

[0036] The obtained Cu-Cr-Zr alloy ingot was cut and sampled, and its cross section was subjected to surface scanning energy spectrum analysis, as shown in the attached Figure 2 When the raw materials are treated to remove the oxide layer and the covering agent and deoxidizer are used, the covering agent can form a dense protective layer on the surface of the alloy melt, isolating the contact between the air and the alloy melt, reducing oxidation and burning, reducing the unevenness of the temperature field in the furnace, and facilitating the uniform distribution and stable existence of the alloy elements; at the same time, the chloride and other components in the composite salt can also react with the moisture in the air to generate corrosive substances such as hydrochloric acid, further inhibiting the oxidation of the alloy elements; adding Cu-Mg deoxidizer, Mg as an active metal, its standard electrode potential is much lower than that of Cu and C r and Zr and other alloy elements; thermodynamically, Mg is more inclined to react with oxygen to form stable oxides, thereby reducing the partial pressure of oxygen in the furnace and slowing down the oxidation and burning of alloy elements; kinetically, in the early stage of smelting, Mg quickly reacts with oxygen to form MgO, and forms a dense magnesium oxide covering layer on the surface of the alloy. This covering layer not only isolates the direct contact between air and the alloy, but also hinders the diffusion of oxygen into the alloy, thereby slowing down the oxidation and burning of Cr and Zr elements, making the recovery rates of Cr and Zr elements as high as 90% and 69% respectively.

[0037] The calculation method and formula of yield are the same as those in Example 1.

[0038] In summary, compared with the traditional melting and casting technology, the recovery rates of Cr and Zr elements using the non-vacuum preparation technology of the present invention can be as high as 90% and 69%.

Claims

1. A preparation method for reducing oxidation and burning loss of active elements during Cu-Cr-Zr alloy smelting, characterized in that Including material preparation, refining and casting processes, specifically including: A. Material preparation: according to the composition design requirements, weigh Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy for use; B. Refining: Bake the furnace, add Cu particles, and add the covering agent when it starts to melt. After all the copper liquid is melted, adjust the temperature to 1150~1250℃; Add deoxidizer Cu-Mg master alloy and fill in covering agent to cover the melt; Add Cu-Cr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1250-1350℃; Add deoxidizer Cu-Mg master alloy again, and add covering agent to cover the melt; Add Cu-Zr master alloy, add covering agent to cover the melt, keep warm and smelt for 20-30 minutes, and adjust the temperature to 1150-1250℃; C. Casting: slag removal and casting to obtain Cu-Cr-Zr alloy.

2. The preparation method according to claim 1, characterized in that The method may further include a step of removing the oxide layer, specifically, electrolytically polishing the Cu particles, Cu-Cr master alloy, Cu-Zr master alloy and deoxidizer Cu-Mg master alloy weighed according to the component design requirements, and then washing and drying them as smelting raw materials for later use.

3. The preparation method according to claim 1, characterized in that The covering agent is composed of charcoal, flake graphite and inorganic composite salt, and has a water content of less than 0.5%.

4. The preparation method according to claim 3, characterized in that In the covering agent component, the mass ratio of charcoal, flake graphite and inorganic composite salt is 1:1:

3.

5. The preparation method according to claim 4, characterized in that The order of adding the components of the covering agent is: first adding the inorganic composite salt as the bottom layer covering, and then adding the charcoal and flake graphite as the upper layer covering, and the total thickness of the covering layer is 2-60 mm.

6. The preparation method according to any one of claims 3 to 5, characterized in that The inorganic composite salt is any one of sodium fluoroaluminate, calcium chloride, sodium chloride or potassium chloride.

7. The preparation method according to claim 1, characterized in that The first addition amount of the deoxidizer Cu-Mg master alloy is 0.5-1% of the mass of the melt; the second addition amount is 0.5-1% of the mass of the melt.

8. The preparation method according to claim 1, characterized in that In the Cu-Cr-Zr alloy, the mass percentage of Cr is 1.0%, the mass percentage of Zr is 0.2%, and the balance is Cu.

9. The preparation method according to claim 1, characterized in that The yield of the Cr element is ≥84%, and the yield of the Zr element is ≥50%.